The Implication of Oxidative Stress and AMPK-Nrf2 Antioxidative Signaling in Pneumonia Pathogenesis - Xu, Weitong; Zhao, Tingting; Xiao, Hengyi (Frontiers in Endocrinology, 2020)
It is widely recognized that chemical, physical, and biological factors can singly or synergistically evoke the excessive production of oxidative stress in pulmonary tissue that followed by pulmonary lesions and pneumonia. In addition, metabolic and endocrine disorder-induced diseases such as diabetes and obesity often expressed higher susceptibility to pulmonary infections, and presented severe symptoms which increasing the mortality rate. Therefore, the connection between the lesion of the lungs and the metabolic/endocrine disorders is an interesting and essential issue to be addressed. Studies have noticed a similar pathological feature in both infectious pneumonia and metabolic disease-intercurrent pulmonary lesions, that is, from the view of molecular pathology, the accumulation of excessive reactive oxygen species (ROS) in pulmonary tissue accompanying with activated pro-inflammatory signals. Meanwhile, Adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) and nuclear factor erythroid-2-related factor 2 (Nrf2) signaling plays important role in metabolic/endocrine homeostasis and infection response, and it's closely associated with the anti-oxidative capacity of the body. For this reason, this review will start from the summary upon the implication of ROS accumulation, and to discuss how AMPK-Nrf2 signaling contributes to maintaining the metabolic/endocrine homeostasis and attenuates the susceptibility of pulmonary infections.